Attenuated Nephritis in Inducible Nitric Oxide Synthase Knockout C57BL/6 Mice and Pulmonary Hemorrhage in CB17 SCID and Recombination Activating Gene 1 Knockout C57BL/6 Mice Infected with Leptospira interrogans - Bandeira, Maurício de Sousa (2014)
Texto completo: acesso restrito. p. 2936-2940